2020
DOI: 10.1186/s13018-020-01782-8
|View full text |Cite
|
Sign up to set email alerts
|

Clubfoot treatment with Ponseti method—parental distress during plaster casting

Abstract: Background: Clubfoot is one of the most prevalent musculoskeletal congenital defects. Gold standard treatment of idiopathic clubfoot is the conservative Ponseti method, including the reduction of deformity with weekly serial plaster casting and percutaneous Achilles tenotomy. It is well known that parents of children with severe and chronic illnesses are mentally stressed, but in recent studies regarding clubfoot treatment, parents were only asked about their satisfaction with the treatment. Largely unknown is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…The other particularity of this intervention during period II was the application of a patient-centered and family-centered method of collaborative care. Indeed, the disorder and its treatment were even discussed during prenatal consultations when the team attempted to identify parents’ concerns and build positive relationships with the families 17 . The Ponseti method’s benefits were explained and emphasized in comparison with the previous technique (posteromedial release).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other particularity of this intervention during period II was the application of a patient-centered and family-centered method of collaborative care. Indeed, the disorder and its treatment were even discussed during prenatal consultations when the team attempted to identify parents’ concerns and build positive relationships with the families 17 . The Ponseti method’s benefits were explained and emphasized in comparison with the previous technique (posteromedial release).…”
Section: Methodsmentioning
confidence: 99%
“…The Ponseti method’s casting phase consists of several manipulations and long leg-casting 17 . Serial casting is done with above-the-knee casts, as below-the-knee casts cannot maintain the foot’s abduction and external rotation.…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 11 , 12 It has been demonstrated to be cost-effective and easy to implement 13 , 14 but requires a strong engagement and resilience from parents as well as the affected child. 15 Non-adherence to the prescribed treatment protocol, including not wearing the brace as often as prescribed, leads to a 5–183-times increased risk of relapse of the deformity. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Prior studies identified barriers to access, treatment, and implementation of clubfoot programs in LMICs. 10 , 23 , 24 , 25 Considering that the Ponseti treatment requires a long-term commitment from the patient as well as the guardian, 15 identifying successful interventions that improve access to treatment is as important as identifying successful policies that help parents and children stay enrolled and finish treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In one of these studies, parents were asked to state their feelings about their child's foot deformity; another study examined the parents' stress and anxiety levels before and after treatment. [7,8] Unlike previous studies in the literature, the present study used the Depression Anxiety Stress Scale-21 (DASS-21). In the present study, we aimed to investigate the depression, anxiety, and stress status among parents of patients with congenital clubfoot before and after treatment with the Ponseti method.…”
Section: Introductionmentioning
confidence: 99%